Synchronous or metachronous metastatic cutaneous cell carcinoma and lymphoma/cronic lymphocytic leukaemia: Considerations for management - Valentina Terenzi; Veronica Clemenzi; Salvatore Martellucci; Andrea Stolfa; Fiorenza Dal Cortivo; Danilo Di Giorgio; Alberto DellAquila; Mattia Di Bartolomeo; Marco Della Monaca; Andrea Battisti; Paolo Priore; Andrea Gallo; et al. (Oral Oncology Reports)
Cutaneous squamous cell carcinoma is not uncommon in patients affected by malignant lymphoma, mostly in elderly; the contemporary management of these diseases presents some difficulties, since they require different modalities of treatment. Only small case series and single case report are described in literature about synchronous or metachronous metastatic cutaneous cell carcinoma and lymphoma/chronic lymphocytic leukaemia; in addiction, we report our experience in order to illustrate difficulties encountered in the management of these patients. We conclude that these patients need a close follow-up, and that US-guided FNAC and 18F-fluorodeoxyglucose PET in addiction to MRI are useful for staging. cSCC, having a poorer prognosis, has to be treated first; nevertheless, mortality in these patients is obviously higher than expected in immunocompetent people.